Gene expression analysis in relation to fusarium wilt resistance in banana (Musa spp.) - Jusna Mariya P L (Centre for Plant Biotechnology and Molecular Biology, College of Horticulture, 2013)
Banana is one of the important fruit crops of India. Banana is susceptible to several fungal pathogens, nematodes, viruses and insect pests. The greatest threats to global banana production is Fusarium wilt or Panama wilt caused by Fusarium oxysporum f. sp. cubense. Control of the pathogen is difficult and mainly involves the use of disease free suckers. Although disease resistance exists in some banana cultivars, introducing resistance into commercial cultivars by conventional breeding is difficult due to its triploid nature and sterility factors of banana. The study entitled "Gene expression analysis in relation to Fusarium wilt resistance in banana (Musa spp.)" was carried out at the Centre for Plant Biotechnology and Molecular Biology, Vellanikkara during the period 2009-2013 with an objective to identify differentially expressed genes in disease resistant genotype of banana, Palayankodan using the molecular technique called suppression subtractive hybridization (SSH). Total RNA and mRNA were isolated from healthy and inoculated plants (with Fusarium oxysporum f.sp. cubense) and were used respectively as 'driver' and 'tester' in SSH reaction. The reactions were performed utilizing the PCR select" cDNA subtraction kit provided by CLONTECH, USA. Control subtraction was carried out first using PCR select" cDNA subtraction kit, which gave satisfactory and expected results. For experimental subtraction, the double stranded cDNAs synthesized from Zug mRNA from normal 'driver' and treated 'tester' were digested with RsaI enzyme. Two tester populations were created and each ligated to two different adaptors. This was followed by two hybridization reactions and finally a selective PCR amplification. Only differentially expressed cDNAs were amplified exponentially. This was confirmed by analyzing the PCR products on agarose gel, which showed a smear ranging from 0.9 to 1.3 kb in the subtracted sample and was different from smear